Network pharmacology and experimental study of Angelica sinensis and Astragalus membranaceus capsules in treating heart failure - Xue Wu; Ai Liu; Xinfang Lv; Xiaodong Zhi; Xiangting Zeng; Kai Liu; Xinke Zhao; Bing Jiang; HuGang Jiang; Yingdong Li (Heliyon)
Objective: This study explores the mechanism of AAC in intervening heart failure (HF) using network pharmacology, molecular docking, and in vitro experimental validation. Methods: The “active component-target” network and the “drug-disease target” protein interaction network were constructed using Cytoscape 3.9.0 and STRING Database. GO and KEGG enrichment analysis was performed using DAVID database. Then, the molecular docking of major compounds and target proteins was carried out using Autodock 1.5.7, and visualized with PyMOL 2.4.0 software. Finally, in vitro experimental validation was performed to explore the potential targets of AAC in treating HF. Results: The study revealed significant targets implicated in a variety of GO bioprocess programs and KEGG signaling networks. The primary chemicals to have strong binding ability with target proteins in molecular docking, with quercetin having the best binding energy with MAPK at −6.72 Kcal/Mol.Validation of cellular experiments showed that AAC might reduce the apoptosis that doxorubicin causes in AC16 cells by controlling the levels of PIK3CA, AKT1, and MAPK1. Conclusion: This study preliminarily reveals that AAC can treat HF through multiple components and multiple targets by using network pharmacology, molecular docking, and experimental validation.